Climate risk management for the U.S. cellulosic biofuels supply chain - Matthew Langholtz; Erin Webb; Benjamin L. Preston; Anthony Turhollow; Norman Breuer; Laurence Eaton; Anthony W. King; Shahabaddine Sokhansanj; Sujithkumar Surendran Nair; Mark Downing (Climate Risk Management, 2014)
As U.S. energy policy turns to bioenergy, and second-generation biofuels in particular, to foster energy security and environmental benefits, consideration should be given to the implications of climate risk for the incipient bioenergy industry. As a case-in-point, we review evidence from the 2012 U.S. drought, underscoring the risk of extreme weather events to the agricultural sector in general, and the bioenergy supply chain in particular, including reductions in feedstock production and higher prices for agricultural commodities and biofuels. We also use a risk management framework developed by the Intergovernmental Panel on Climate Change to review current understanding regarding climate-related hazards, exposure, and vulnerability of the bioenergy supply chain with a particular emphasis on the growing importance of lignocellulosic feedstocks to future bioenergy development. A number of climate-related hazards are projected to become more severe in future decades, and future growth of bioenergy feedstocks is likely to occur disproportionately in regions preferentially exposed to such hazards. However, strategies and opportunities are available across the supply chain to enhance coping and adaptive capacity in response to this risk. In particular, the implications of climate change will be influenced by the expansion of cellulosic feedstocks, particularly perennial grasses and woody biomass. In addition, advancements in feedstock development, logistics, and extension provide opportunities to support the sustainable development of a robust U.S. bioenergy industry as part of a holistic energy and environmental policy. However, given the nascent state of the cellulosic biofuels industry, careful attention should be given to managing climate risk over both short- and long-time scales.